“Here in the Bible Belt, It’s Predominantly Negative”: Sexual Identity Stigma in the American South, 50 Years After Stonewall - Frey, Joseph J.; Hall, William J.; Goldbach, Jeremy T.; Lanier, Paul (Frontiers in Psychology, 2021)
Lesbian, gay, bisexual, and pansexual (LGB+) individuals have disproportionate rates of mental illness. Minority stress and sexual identity stigma are posited as the primary social determinants of LGB+ mental health disparities. Discussions in the literature have questioned the impact of sexual identity stigma in a world increasingly accepting of sexual minorities. Additionally, the LGB+ population in the U.S. South is often overlooked in American research. This article details a qualitative study exploring sexual identity stigma among adults who identify as LGB+ in the U.S. South. Semi-structured interviews with 16 individuals were analyzed using content analysis. Six thematic categories of stigma emerged from participants’ experiences: (a) navigating an LGB+ identity, (b) social acceptability of an LGB+ identity, (c) expectation of LGB+ stigma, (d) interpersonal discrimination and harassment, (e) structural stigma, and (f) relationship with the lesbian, gay, bisexual, transgender, and queer (LGBTQ) community. Findings suggest that sexual identity stigma remains a common experience among these Southern U.S. participants. Further, thematic categories and subcategories primarily aligned with extant theory with one exception: Intracommunity stigma, a form of stigma emanating from the LGBTQ community, emerged as a stigma type not currently accounted for in theoretical foundations underpinning mental health disparities in this population.